Sintering of Functional Materials 2018
DOI: 10.5772/68081
|View full text |Cite
|
Sign up to set email alerts
|

Development of Metal Matrix Composites Using Microwave Sintering Technique

Abstract: In this book chapter, aluminum (Al)-based metal matrix composites (AMMCs) with various reinforcing ceramic particles, such as SiC, Si 3 N 4 , and Al 2 O 3 , were produced by microwave sintering and subsequent hot extrusion processes. The role of various nano/ micro-sized reinforcements in altering the structural, mechanical, and thermal properties of the microwave-extruded composites was systematically studied. The X-ray diffraction (XRD) patterns indicated that the main components were Al, SiC, Si 3 N 4 , and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 44 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Good fracture toughness parameters for 2 wt.-% mixed Al 2 O 3 and Si3N4 were found in comparison to the pure sintered sample. Matli et al 12 prepared Al-based metal From archival literature, it has been observed that most of the automobile manufacturing industries used SiC and Al 2 O 3 as reinforcement with aluminum alloy in the fabrication of different parts. 5 In the present study, Si 3 N 4 is used along with Al 2 O 3 in the partial replacement of SiC.…”
Section: Introductionmentioning
confidence: 99%
“…Good fracture toughness parameters for 2 wt.-% mixed Al 2 O 3 and Si3N4 were found in comparison to the pure sintered sample. Matli et al 12 prepared Al-based metal From archival literature, it has been observed that most of the automobile manufacturing industries used SiC and Al 2 O 3 as reinforcement with aluminum alloy in the fabrication of different parts. 5 In the present study, Si 3 N 4 is used along with Al 2 O 3 in the partial replacement of SiC.…”
Section: Introductionmentioning
confidence: 99%
“…They mixed different contents of CNTs (0.5 to 2.0 wt%) with the metallic powders in isopropanol; upon drying, the mixtures were uniaxially compacted and then sintered at elevated temperatures at different sintering times (i.e., 90 min at 640 • C for Al/CNT nanocomposites and 120 min at 950 • C for Ni/CNT nanocomposites). The PM technique, assisted with a novel "MW sintering" has been used extensively to produce different grades of Mg matrix nanocomposites [43][44][45][46]; MW heating is used to rapidly and effectively heat up the mixed powder particles as heat is generated within the powders, internally, and radiates outward (core-to-surface), which is contrary to what occurs in the conventional sintering process (surface-to-core) [44,45].…”
mentioning
confidence: 99%